Regionalist Legitimation in the Face of Nationalist Irruption: the Logic of the Questions from Vida Gallega to Nacionalismo Gallego. Nuestra afirmación regional as a Case - Torres Feijó , Elias J. (Madrygal. Revista de Estudios Gallegos, 2023)
The emergence of new or renewed ideas in a system or amphysystem that propose and are the object of action for its implementation may lead to relevant changes within it. Occasionally, it is about the impulse and nuance of already existing ideas whose success will depend on their ability to condition systemic activity and its scope. To this end, it is not infrequent that certain dominant groups attempt to negotiate new proposals in various directions; among these is the reformulation of the proposed concepts and ideas as part of the existing and status quo or the limitation of the scope of those proposals to positions and functions that do not threaten their centrality. In this case, this was the reality of the reception of the magazine Vida Gallega, representative and, above all, a journalistic model of that centrality, to the publication of Nacionalismo Gallego. Nuestra afirmación regional, by Antonio Villar Ponte. The text analyzes the logic of the proposals and the first debate, which takes place given the already relevant position of Antonio Villar Ponte and the framework of situation conducive to the consideration of regionalism/nationalism in Galicia, its dimensions and intended effects. It is these circumstances that explain why Villar Ponte and the Irmandades were able to place Galicanship as central to the Galician amphysystem and why sectors such as those represented by Vida Gallega had to take them into account, even incorporating, in the future, elements of the proposed new Galicanship. That logic still works as a substrate in today’s Galicia.
Keywords: Antonio Villar Ponte; Vida Gallega; Galicianism; 1916; Negotiation; Amphysystem